1994
DOI: 10.1029/94rs01350
|View full text |Cite
|
Sign up to set email alerts
|

Three years of C band signal measurements for overwater, line‐of‐sight links in the mid‐Atlantic coast: 2. Meteorological aspects of sustained deep fades

Abstract: The morphology of deep and long‐lived fades for line‐of‐sight, overwater propagation links in the mid‐Atlantic coast are examined. Such events, known as sustained deep fades (SDF), are analyzed employing weather maps, in situ measurements from radiosondes, an instrumented helicopter, and sensors on coastal platforms. These events occurred exclusively from November through July over the 3 years in which fade statistics were amassed; no SDF events were observed during the months August, September, or October. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Application to higher-altitude antennas (i.e., above 45.5 m) would implicitly be assuming that the refractivity profiles contributing to the derived distributions continued to have subrefractive gradients at higher altitudes. In fact, refractivity profiles measured during subrefractive events suggest that the subrefractive layer has a typical height of 100-300 m, above which the refractive profile is standard [Goldhirsh et al, 1994b;Babin, 1995].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Application to higher-altitude antennas (i.e., above 45.5 m) would implicitly be assuming that the refractivity profiles contributing to the derived distributions continued to have subrefractive gradients at higher altitudes. In fact, refractivity profiles measured during subrefractive events suggest that the subrefractive layer has a typical height of 100-300 m, above which the refractive profile is standard [Goldhirsh et al, 1994b;Babin, 1995].…”
Section: Discussionmentioning
confidence: 99%
“…An examination of weather maps during severe subrefractive events have, however, demonstrated that this phenomenon does extend over significant portions of the east coast of the United States [Goldhirsh et al, 1994b].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the availability of advected subtropical moisture at the higher altitudes, a local increase of water vapor pressure usually occurs. This combination of temperature and water vapor pressure inversions results in a positive lapse rate of the refractivity and the condition of extreme subrefraction [Goldhirsh et al, 1994b]. This type of phenomenon affects not only communications but also radar detection capabilities.…”
Section: Effects Of Evaporation Ducts On Propagation Factormentioning
confidence: 99%